Using Virtual Reality to Enhance Surgical Skills and Engagement in Orthopedic Education: Systematic Review and Meta-Analysis - Ting Li; Jingxin Yan; Xin Gao; Hangyu Liu; Jin Li; Yuanting Shang; Xiaoyu Tang (Journal of Medical Internet Research)
Abstract BackgroundCurrently, virtual reality (VR) simulators are of increasing interest for surgical training, but there is no systematic review exploring the advantages and disadvantages of VR in orthopedic education. ObjectiveThis paper aims to explore the relationship between VR education and traditional education. MethodsWe searched PubMed, Embase, Web of Science, Cochrane library, Scopus, Chongqing VIP Database (VIP), Chinese National Knowledge Infrastructure (CNKI), and Wan Fang Database up to July 2024 for relevant studies. A total of 2 investigators independently conducted literature screening, data extraction, and risk of bias assessment for included studies in accordance with the PICOS framework (Population, Intervention, Comparison, Outcomes, and Study Design), followed by statistical synthesis of outcomes using RevMan 5.3 software (Cochrane Collaboration). The risk of bias evaluation adhered to the Cochrane Risk of Bias Tool (RoB 2.0) for randomized controlled trials, ensuring systematic appraisal of sequence generation, allocation concealment, blinding, incomplete outcome data, and selective reporting. ResultsA total of 23 randomized controlled trials included 1091 participants in this meta-analysis. The majority of studies focused on the undergraduates (n=3) and trainees (n=8), resident doctors (n=10), and postgraduate doctors (n=2). A total of 3 studies were missing the age of participants, and 5 studies were also missing the duration data. The main outcome included knowledge scores, clinical operation scores, surgical design scores, and so on. The secondary outcomes were included course participation, learning efficiency, enhance clinical ability, and so on. Compared to traditional teaching, VR interventions resulted in significantly higher knowledge scores (standardized mean difference [SMD]=1.08, 95% CI 0.71-1.46; PPPPPPPP ConclusionsThis meta-analysis emphasizes VR as an excellent orthopedic educational tool. It significantly enhances both theoretical knowledge and practical skills, while also markedly increasing student engagement and satisfaction. Therefore, adopting VR technology in medical education holds promise for improving orthopedic surgical competence. However, the quality of this meta-analysis was limited by the notable heterogeneity in terms of VR platforms these findings and further validation through multicenter, double-blind, and large-sample randomized controlled trials is required.